A demon of our own design : markets, hedge funds, and the perils of financial innovation - Bookstaber, Richard M., 1950- (J. Wiley, 2007)
Inside markets, innovation, and riskWhy do markets keep crashing and why are financial crises greater than ever before? As the risk manager to some of the leading firms on Wall Street-from Morgan Stanley to Salomon and Citigroup-and a member of some of the world's largest hedge funds, from Moore Capital to Ziff Brothers and FrontPoint Partners, Rick Bookstaber has seen the ghost inside the machine and vividly shows us a world that is even riskier than we think. The very things done to make markets safer, have, in fact, created a world that is far more dangerous. From the 1987 crash to Citigrou.